TINJAUAN TERHADAP PENYAMPAIAN SURAT PANGGILAN SIDANG KEPADA TERDAKWA DALAM PERADILAN PERKARA PIDANA DI PENGADILAN NEGERI SAMARINDA - Mikael Paran (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Summons trial in criminal proceedings, both addressed to the defendant or witnesses to be confronted in the face of the trial court is very important, so that the call letters of this trial should really be done properly in accordance with the provisions of the criminal procedure law. Because absentia trial acts may be done and without the presence of the accused may follow dilkaukan session without the presence of witnesses is also not possible verification can be done.Based on the development of delivery of summons palaksanaan practice session conducted Samarinda clearly aligned with the state judiciary law application delivery events divulging call this trial is still experiencing some obstacles. That the delivery of summons hearing officer in this case the Prosecution has not been fully able to carry out their duties in the delivery of a subpoena, which is where it is evident from the number of people, especially who are called to be witnesses of the goals and objectives it to avoid a trial. That given the importance of summons hearing criminal cases in the judicial process, would still need to be increased awareness and technical knowledge of the public prosecutor in carrying out tasks summons trial. And society in particular defendant or witness would still need to be increased awareness and knowledge of the law, which this is done, such as providing extension through KADARKUM program and outreach programs in the community.